Biocatalytic Dynamic Kinetic Resolution for the Synthesis of Atropisomeric Biaryl N‐Oxide Lewis Base Catalysts. Issue 36 (9th August 2016) - Staniland, Samantha; Adams, Ralph W.; McDouall, Joseph J. W.; Maffucci, Irene; Contini, Alessandro; Grainger, Damian M.; Turner, Nicholas J.; Clayden, Jonathan
Abstract: Atropisomeric biaryl pyridine and isoquinoline N‐oxides were synthesized enantioselectively by dynamic kinetic resolution (DKR) of rapidly racemizing precursors exhibiting free bond rotation. The DKR was achieved by ketoreductase (KRED) catalyzed reduction of an aldehyde to form a configurationally stable atropisomeric alcohol, with the substantial increase in rotational barrier arising from the loss of a bonding interaction between the N‐oxide and the aldehyde. Use of different KREDs allowed either the M or P enantiomer to be synthesized in excellent enantiopurity. The enantioenriched biaryl N‐oxide compounds catalyze the asymmetric allylation of benzaldehyde derivatives with allyltrichlorosilane. Abstract : Speedy resolution : Enzymatic reduction of rapidly racemizing biaryl aldehydes yields, by highly selective dynamic kinetic resolution (DKR), single enantiomers of atropisomeric biaryls in high yield and with high ee values. This first atropselective enzymatic DKR gives products that contain a pyridine N‐oxide and primary alcohol groups and function as catalysts of asymmetric aldehyde allylation.